PENGARUH JASA LAYANAN, HARGA, PROSES TERHADAP KEPERCAYAAN DAN PERILAKU PENGGUNAAN ULANG MASYARAKAT PADA ADVOKAT DI KABUPATEN JEMBER - Widhiarti, Any (BISMA: Jurnal Bisnis dan Manajemen, 2016)
Abstract : This study aims to examine the effect of service, price, process on trust and behavior of community reuse at Advocate in Jember Regency. Type of research with quantitative approach, sample 114 clients who need assistance 5 services advocate registered in PERADI Jember District. The analysis tool is data analysis model with Assumption Structural Equation Modeling (SEM) Test. Result of research, that is: (1) service, price, and process have significant influence to public trust in Advokat in Jember Regency; (2) services, prices, and processes have a significant effect on the behavior of community reuse at Advocate in Jember District. Keywords : Services , price, process on trust , re-use behavior